Challenges facing women in the labor market: Are there solutions on the horizon? | تحديات تواجه المرأة في سوق العمل: هل من حلول في الأفق؟ - Massoud M. AlShareef | مسعود محمد الشريف (Publishing and Public Relation Department | إدارة النشر والعلاقات العامة, 2024)
Unfortunately, these challenges are like worries weighing on women’s chests, seemingly endless. They include almost everything, which prompts the question: Is this material enough to list them? Of course not. Let us try to summarize them as much as possible, based on the experience of the writer, one of the Arab women who are trying to overcome these challenges. | للأسف تلك التحديات بمثابة همومٍ جاثمةٍ فوق صدور النَّساء، تبدو وكأن ليس لها نهايةٌ، إنِّها تشمل كلَّ شيءٍ تقريباً، ما يدفع للتَّساؤل، هل تكفي مادتنا هذه لسردها؟ بالطَّبع لا، دعونا نحاول تلخيصها ما أمكن، انطلاقاً من تجربة الكاتبة، إحدى النساء العربيَّات اللَّواتي يحاولنّ تجاوز هذه التَّحدِّيات.